Long-Term Care System in Slovakia - Gerda SCHMAHL (Communications of International Proceedings, 2021)
A comparison of European care systems reveals striking differences in the construction and design of the national systems. Declining relative size of the working-age population, decreasing family-based care supply due to higher female labor force participation, and reduced family size will increase the demand and cost of long-term care (LTC). While research on the Slovak LTC system is in its beginnings, this paper aims to contribute to the acquisition of more knowledge about LTC systems within the European Union and, in particular, to present how the social and financial risk of LTC dependency is covered in the Slovak Republic. The paper organizes existing literature on organization, access, infrastructure and financing of LTC and uses it to analyze the economic, policy and behavioral forces that underpin the observed equilibrium. The Slovak Republic presents a family-based LTC system with a social security system in the process of being established. The lack of services and the financing of the LTC system are insufficiently prepared for the demand, which is expected to rise in the coming years concurrent with the aging of Slovakia's population.
Keywords: Long-Term Care; Access; Financing; Slovakia